Discovering the Postdoctoral Research Fellow (PDRF) Sector at UCT with a view to improving the PDRF experience - Hendry, Jane; Vranas, Linda (South African Journal of Higher Education, 2016)
The postdoctoral research fellow (PDRF) sector at the University of Cape Town (UCT) is a growing one, and provides a significant contribution to the institutional research endeavour. Until 2002, this sector was unregulated and the experiences of PDRFs were largely unknown. Since then a range of regulatory developments have taken place and two surveys have been carried out in order to understand the issues and challenges faced by the PDRFs, with a view to putting in place interventions to enhance their experience at UCT. This paper provides a brief, post-2002 history of the PDRF sector at UCT, describes the survey methodology used and results obtained, and reports on some of the interventions that have flowed from the survey findings. The paper also reflects on the effectiveness of the (institutional) research – intervention – further (institutional) research method employed here, and on the importance of embedding of the work of this kind within the business of relevant institutional committee structures.